Catalysis Using Sustainable Metals – Part I - Gaunt, Matthew; Rovis, Tomislav; Chow, Hak-Fun (Synlett, 2014)
The discovery of new catalytic reactions involving the use of abundant, inexpensive and sustainable metal complexes has enjoyed a resurgence of activities in recent years. This Cluster, Part I of a two-part series, focuses on new research findings from several prominent research groups, highlighting the rich diversities of new chemistry that can be originated from the use of sustainable metals in catalytic reactions.
Keywords: sustainable metal; catalysis; cycloaddition; aminoxylation; dimerization; quinolone; S-arylation; biomass conversion